Penerapan Quality Function Deployment (QFD) dalam Upaya Peningkatan Kualitas Layanan Air Conditioner di CV. XYZ - Fahruddin , Muhammad; Rizqi, Akhmad; Jufrianto, Moh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This research focuses on the quality of service available at CV company AC service companies. XYZ, which is in Dukun District, uses the QFD (Quality Function Deployment) method using data processing from questionnaires, interviews and surveys. shows the customer's desire rating for the company to lower the marketed price slightly so that customers do not change to other services.